Computer Network Analysis Using The Queue System In Mikrotik: Computer Network Analysis Using The Queue System In Mikrotik - M. Khairun Nur Al Fadjri; Ritzkal Ritzkal; A Hendri Hendrawan (Jurnal Mantik, 2020)
Nowadays the development of the internet has been very rapid along with its development, internet traffic has become very dense. Therefore an administrator must be very clever to do bandwidth management. Bandwidth management is very important in managing bandwidth allocation that will be given to users to avoid struggling for bandwidth allocation on the network. By using a proxy router, an administrator can easily do that, however, within the proxy router, there are several queuing methods that can be used to manage bandwidth. the purpose of this study is (i) Can implement bandwidth management using the queue system on the router, (ii) Can know the queuing system testing to handle network traffic using a router. The research methods used are identification, design, implementation and testing. The results obtained are the best transfer rate with a total value of 112.7216 KB/second using the BFIFO queuing system. The smallest bytes queue is PCQ with a total value of 276.8 MiB and the most is SFQ with a total value of 283.4 MiB, the smallest queue of packets is RED with a total value of 220861 packets and the most is BFIFO with a total value of 225414 packets.